Role of PKM2-Mediated Immunometabolic Reprogramming on Development of Cytokine Storm - Liu, Zhijun; Le, Yifei; Chen, Hang; Zhu, Ji; Lu, Dezhao (Frontiers in Immunology, 2021)
The cytokine storm is a marker of severity of various diseases and increased mortality. The altered metabolic profile and energy generation of immune cells affects their activation, exacerbating the cytokine storm. Currently, the emerging field of immunometabolism has highlighted the importance of specific metabolic pathways in immune regulation. The glycolytic enzyme pyruvate kinase M2 (PKM2) is a key regulator of immunometabolism and bridges metabolic and inflammatory dysfunction. This enzyme changes its conformation thus walks in different fields including metabolism and inflammation and associates with various transcription factors. This review summarizes the vital role of PKM2 in mediating immunometabolic reprogramming and its role in inducing cytokine storm, with a focus on providing references for further understanding of its pathological functions and for proposing new targets for the treatment of related diseases.